The Effectiveness Of Community Mental Health Counseling On The Mental Health Of Farmers During The Covid-19 Pandemic - Budiman, M.Elyas Arif; Yuhbaba, Zidni Nuris; Silvanasari, Irwina Angelia; Erdah Suswati, Wahyi Sholehah; Basri, Achmad Ali (Jurnal EduHealth, 2022)
The spread of the COVID-19 pandemic creates new stressors for farmers and creates pressure and uncertainty for farmers and has a negative impact on the mental health of farmers and the wider Community. In connection with these problems, one of the actions that can improve mental health in farmers is health counselling.The purpose of this study was to determine community-based counseling on the mental health of farmers during the covid-19 pandemic. The type of research used in this study is a quasi-experimental with a sample of 80 respondents with purposive sampling technique. The measuring instrument uses a Self-Reporting Questionnaire (SRQ). Data analysis used the Wilcoxon Paired test and the Mann Whitney test.The results of the Wilcoxon test in this study showed that the experimental group had a p value of 0.00 and in the control group a p value of 180 then the two groups were tested differently using the Mann Whitney test showing a p value of 0.00 where these results indicate that there is an effect of counseling community based on the mental health of farmers during the Covid-19 pandemic. The uncertainty of Covid-19 coupled with the new social environment makes it even more important to understand the importance of mental health counseling for farmers in rural areas to help support farmers in adapting to the habits of the Covid-19 pandemic.